Poggio al vento la prima casa solare in Toscana - Windy hill the early solar house in Tuscany - Esposito, Maria Antonietta (Strumenti per la didattica e la ricerca, 2012)
The book reconstructs the story of a small but interesting project by the architect Pier Luigi Spadolini and, in unpublished documents, proposes a new reading by the technology that reveals some surprising connections. The research design is conducted and driven by a path that crosses the history of a major industrial company in the Tuscany territory now multinational. In this context this precursor project brings to a strong focus on the environment and that after 25 years could be defined as an early solar energy retrofit project.